Review on extraction and application of natural dyes - Salauddin Sk, Md (Array, 2021)
With the improvement of living standards, everybody is very much conscious about the environmental protection and health safety. Natural dyes have attracted more attention to the industry due to exhibiting better biodegradability and more compatibility with the environment. Characteristic colours that are gathered from common assets can be categorized as either plant, creature, mineral, or microbial colours and can be used for colouring a wide range of regular filaments. Late examination shows that it can likewise be utilized to colour a portion of the manufactured filaments too. Normal colours are not just utilized in the shading of material filaments, they are also utilized for food, prescriptions, handiwork articles, and leather preparing. Extraction and purification play a vital role in the processing of natural dyes. There are different types of extraction process currently available for these natural dyes, such as solvent extraction, aqueous extraction, enzymatic extraction and fermentation, extraction with microwave or ultrasonic energy, supercritical fluid extraction, and alkaline or acid extraction. All these extraction processes have their own advantages as well as some drawbacks depending on the parameters that need to be maintained during the extraction process. Appropriate extraction can be beneficial for specific types of such dyes. In this paper, the classification, characteristics, extraction methods, and the application of natural dyes are introduced in an organized manner.